Teknik dan Instrumen Asesmen Ranah Kognitif - Dedi Rosyidi (LPPM STAI Ihyaul Ulum Gresik, 2020)
The assessment seeks to determine whether the educational objectives are achieved or not, so that the evaluation has a very large role in the world of education. Effective and efficient evaluation is carried out continuously and throughout it is expected that educators can get a full picture of the achievements and progress of the process and learning outcomes achieved by the learners. Each subject emphasizes continuous evaluation, referring to comprehensive goals and results. There are several among the areas of assessment in education is the cognitive realm. Cognitive assessment is an activity carried out to measure the mastery of knowledge of learners. Assessment of cognitive aspects is carried out through stages: develop assessment planning, develop assessment instruments, carry out assessments, utilize assessment results, and report assessment results in the form of numbers with a scale of 0-100 and description.